2018
DOI: 10.1177/1747021818806491
|View full text |Cite
|
Sign up to set email alerts
|

Age-related effects in compound production: Evidence from a double-object picture naming task

Abstract: This study investigated effects of healthy ageing and of non-verbal attentional control on speech production. Young and older speakers participated in a picture-word interference (PWI) task with compound targets. To increase the processing load, the two pictures of the compounds’ constituents were presented side-by-side for spoken naming (e.g., a picture of a sun + a picture of a flower to be named with sunflower). Written distractors either corresponded to the first or second constituent ( sun or flower → sun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 83 publications
(149 reference statements)
0
3
0
Order By: Relevance
“…While many studies have also reported agerelated decreases in accuracy rates, the picture is less uniform than for RTs. Accuracy declines are found most reliably in tasks tapping word recall from meaning (e.g., naming from pictures or definitions, or semantic fluency; Au et al, 1995;Bowles & Poon, 1985;Brickman et al, 2005;Burke & Shafto, 2008;Connor, Spiro, Obler, & Albert, 2004;Gollan, Montoya, Cera, & Sandoval, 2008;Hodgson & Ellis, 1998;Lorenz, Regel, Zwitserlood, & Abdel Rahman, 2018;Lorenz, Zwitserlood, Regel, & Abdel Rahman, 2019;Morrison, Hirsh, & Duggan, 2002;Mortensen et al, 2006;Newman & German, 2005;Nicholas, Obler, Albert, & Goodglass, 1985;Nicholas, Obler, Au, & Albert, 1996;Shafto, Burke, Stamatakis, Tam, & Tyler, 2007). In contrast, meaning-based recognition tasks (e.g., word-picture matching ;Facal, Juncos-Rabadán, Rodríguez, & Pereiro, 2012;Feyereisen et al, 1998;Uttl, 2002;Verhaeghen, 2003) and form-based recall or recognition tasks (e.g., pronunciation, lexical decision) usually show no age-related declines in accuracy or even accuracy increases (Allen, Bucur, Grabbe, Work, & Madden, 2011;Allen, Madden, & Crozier, 1991;Allen, Madden, Weber, & Groth, 1993;Balota et al, 2004;Balota & Ferraro, 1996;Bowles & Poon, 1981Cohen-Shikora & Balota, 2016;Ratcliff, Thapar, Gomez, & McKoon, 2004;Reifegerste et al, 2019;Robert & Mathey, 2007;Tainturier, Tremblay, & Lecours, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…While many studies have also reported agerelated decreases in accuracy rates, the picture is less uniform than for RTs. Accuracy declines are found most reliably in tasks tapping word recall from meaning (e.g., naming from pictures or definitions, or semantic fluency; Au et al, 1995;Bowles & Poon, 1985;Brickman et al, 2005;Burke & Shafto, 2008;Connor, Spiro, Obler, & Albert, 2004;Gollan, Montoya, Cera, & Sandoval, 2008;Hodgson & Ellis, 1998;Lorenz, Regel, Zwitserlood, & Abdel Rahman, 2018;Lorenz, Zwitserlood, Regel, & Abdel Rahman, 2019;Morrison, Hirsh, & Duggan, 2002;Mortensen et al, 2006;Newman & German, 2005;Nicholas, Obler, Albert, & Goodglass, 1985;Nicholas, Obler, Au, & Albert, 1996;Shafto, Burke, Stamatakis, Tam, & Tyler, 2007). In contrast, meaning-based recognition tasks (e.g., word-picture matching ;Facal, Juncos-Rabadán, Rodríguez, & Pereiro, 2012;Feyereisen et al, 1998;Uttl, 2002;Verhaeghen, 2003) and form-based recall or recognition tasks (e.g., pronunciation, lexical decision) usually show no age-related declines in accuracy or even accuracy increases (Allen, Bucur, Grabbe, Work, & Madden, 2011;Allen, Madden, & Crozier, 1991;Allen, Madden, Weber, & Groth, 1993;Balota et al, 2004;Balota & Ferraro, 1996;Bowles & Poon, 1981Cohen-Shikora & Balota, 2016;Ratcliff, Thapar, Gomez, & McKoon, 2004;Reifegerste et al, 2019;Robert & Mathey, 2007;Tainturier, Tremblay, & Lecours, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Our participants might therefore have noticed the morphological structure of the compounds, particularly when presented after the simple words, and might have processed their constituents more consciously. Previous research has shown that awareness of the constituents leads to different processing of lexicalized compounds, rendering the constituent representations more salient and thus more highly activated (e.g., Lorenz et al, 2019). To test this idea, we ran an analysis including the order in which participants named the two word-type conditions as factor.…”
mentioning
confidence: 99%
“…For example, correlations between measures of sustained attention and picture naming speed have been reported (Jongman, 2017;. Other studies have observed relationships between working memory measures and picture naming latencies (Piai & Roelofs, 2013;Shao, Roelofs, & Meyer, 2012; but see Klaus & Schriefers, 2018), and a few studies have found that inhibition skills are related to picture naming speed (Lorenz, Zwitserlood, Regel, & Abdel Rahman, 2019;Shao, Meyer, & Roelofs, 2013;Sikora, Roelofs, Hermans, & Knoors, 2016).…”
mentioning
confidence: 99%